THE EFFECT OF VERBAL VIOLENCE ON SELF-CONFIDENCE AND LEARNING OUTCOMES OF VINTAGE VOCATIONAL SCHOOL STUDENTS IN CLASS V SD NEGERI 83 SINGKAWANG - Nelly Agustin; Zulfahita Zulfahita; Wasis Suprapto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2023)
This study aims to determine the effect of verbal violence on self-confidence and learning outcomes of PPKn grade V students. This research was conducted at SD Negeri 83 Singkawang. The type of research used is quantitative research with a simple regression method. The population in this study were fifth-grade students at SD Negeri 83 Singkawang. This study uses a type of total sampling, namely the sample taken is the entire population. The prerequisite test is the normality test using the chi-square formula and the linearity test to find out whether the two or more variables tested have a linear relationship or not. The data were analyzed with a significance level of 5% (0.05), to test the hypothesis using a simple regression test. The results showed that: 1) There was an influence of verbal violence on the self-confidence of fifth-grade students. The calculation results obtained F_count > F_table, namely F_count = 4.8694 > F_table = 4.17, then Ha was accepted and HO was rejected; 2) There is an influence of verbal violence on the learning outcomes of Grade V PPKn students. The calculation results are obtained F_count > F_table, namely F_count = 4.6325 > F_table = 4.17, then Ha is accepted and HO is rejected.